1999
DOI: 10.1029/1999gb900044
|View full text |Cite
|
Sign up to set email alerts
|

Human impacts on the large world rivers: Would the Changjiang (Yangtze River) be an illustration?

Abstract: Abstract. The "Three Gorges Project" (TGP) in the upstream of Changjiang (Yangtze River) has resulted in great concern of scientific society and public conversations on the economic, environmental, and human health issues. Data of nutrients from main stream and 15 large tributaries indicate that Changjiang receives a large part of its nutrient burden from the drainage area upstream the "Three Gorges Dam" (TGD). A model calculation shows that the construction of TGD may cause further eutrophication in the upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(103 citation statements)
references
References 15 publications
3
89
2
4
Order By: Relevance
“…Duan et al (2007) Today, we observed DIP concentrations on a much lower and constant concentration of 6-8 µgP/L compared to 10-25 µgP/L reported by Zhang et al (1999) a decade ago. However, contrary to the prior observations, NO 3 − concentrations steadily increased downstream of the TGD (Fig.…”
Section: Nutrients: N and Pmentioning
confidence: 51%
See 2 more Smart Citations
“…Duan et al (2007) Today, we observed DIP concentrations on a much lower and constant concentration of 6-8 µgP/L compared to 10-25 µgP/L reported by Zhang et al (1999) a decade ago. However, contrary to the prior observations, NO 3 − concentrations steadily increased downstream of the TGD (Fig.…”
Section: Nutrients: N and Pmentioning
confidence: 51%
“…5). The comparison of results may be biased by the lower water discharge during our expedition (November) than of the measurements by Zhang et al (1999) (April-May 1997. However, the new pattern may be caused by reforestation efforts in the Jialingjiang watershed (Yang et al, 2006b), which reduced soil erosion and, hence, nutrient input, and the accumulation of water and particles in the TGD reservoir.…”
Section: Nutrients: N and Pmentioning
confidence: 74%
See 1 more Smart Citation
“…As far as the Yangtze estuary was concerned, the local rainfall contributed to 0.74% of the DIN influxes in dry season and 0.64% of the DIN influxes in flood season in 1999 based on our nutrient budget. But for the whole Yangtze River basin, the rainfall contributed much to the nutrient fluxes, especially for DIN (Shen Estimated roughly from the figure data of Zhang et al (1999) c Derived from nitrate fluxes provided the ratio between nitrate and DIN is 80% (73.9-95.5%, Fu et al 2002) Fig The nitrate fluxes to the estuary from the Yangtze River basin, correlated well with the mean rainfall (r=0.80; n=144), increasing with increasing rainfall in the basin. Compared to nitrogen, wet deposition often played a minor role in the process of P deposition.…”
Section: Atmospheric Depositionmentioning
confidence: 99%
“…1) from the Yangtze River basin . The concentrations and fluxes of dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphorus (DIP) have substantially increased in the Yangtze River and its estuary in the last 20 years (Zhang et al 1999;. The additional inputs of nutrients account for the considerable eutrophication and frequent algae booms in this estuary and its adjoining East China Sea in recent years.…”
Section: Introductionmentioning
confidence: 99%